Pocket-size ultrasound devices may improve the prompt assessment of Covid-19 patients. (14th October 2021) - Filipiak, D; Kasprzak, J D; Lipiec, P
Abstract: Introduction: Clinical usefulness of pocket-size ultrasound device [PSUD] was previously confirmed in numerous clinical scenarios. During the previous year Covid-19 patients have become a focal point of the cardiology and internal medicine wards. However, there is no data on the use of PSUD in this scenario. Purpose: To asses if PSUD may be useful in providing additional information in Covid-19 patients. Methods: In 63 patients (41 men, mean age 63±11) with confirmed Covid-19 the scope of physical examination was expanded with bedside assessment performed with PSUD equipped with dual probe. PSUD examination included: right ventricle measurement, automated LVEF assessment, 4-point compression ultrasound test of lower limbs and lung ultrasound (presence of B-lines, lung consolidations or thickening of pleura). Subsequently, within the next 24 hours all patients underwent chest CT scan, CT pulmonary angiogram and full echocardiographic examination performed on a high-end stationary device. Results: Lung lesions typical for Covid-19 were confirmed in CT in 53 (84%) patients. The sensitivity and specificity of bedside PSUD examination for diagnosing lung involvement was 92% and 90%, respectively, when presence of any pathology on lung ultrasound was considered as a positive criterion. Increased number of B-lines had a sensitivity of 81%, specificity 83% for the ground glass symptom in CT detection, (AUC 0, 82; p<0, 0001). Pleural thickening was diagnosed by PSUD with a 95% sensitivity and 88% specificity (AUC 0, 91, p<0, 0001), whereas lung consolidations with a 71% sensitivity and 86% specificity (AUC 0, 79, p<0, 0001). In 20 patients (32%) pulmonary embolism was confirmed by angioCT – in 10 among them embolism was limited to subsegmental arteries. RV was found to be dilated in PSUD examination in 27 patients (43%), CUS was positive in 1 patient. Thus, RV enlargement treated as a marker of PE had low sensitivity and specificity (60% i 65% respectively), AUC=0, 62, p=0, 06. Mean LVEF in standard echocardiography was 46±12%, but during PSUD examination automated LV function analysis software failed to calculate LVEF in 29 (46%) cases due to suboptimal image quality. Conclusion: In Covid-19 patients PSUD is particularly useful for lung ultrasound and the detection of lung pathologies. RV enlargement observed during PSUD examination has relatively low sensitivity and specificity for the detection of pulmonary embolism in Covid-19. Furthermore, due to low quality of images automated LV function assessment failed to provide any result in almost half of patients. FUNDunding Acknowledgement: Type of funding sources: None.